Editorial: Optimizing nutrition from the inside out: innovations in digestion, fermentation, and functional food processing - Naderi, Nassim (Frontiers in Food Science and Technology, 2025)
Graphical AbstractOptimizing Nutrition from the Inside Out: Innovations in Digestion, Fermentation, and Functional Food Processing is depicted in a graphic divided into four sections. Each section includes an icon and a title with a brief explanation. Valorization of By-Products with stacked circles icon focuses on repurposing food waste into nutritional ingredients. Digestion and Bioavailability with a human silhouette icon aims at enhancing nutrient absorption. Encapsulation Technologies with a capsule icon targets improving the stability and delivery of bioactive compounds. Microbiota Modulation with a microorganism icon centers on influencing gut health via dietary interventions.